Clinical outcomes and risk factors in pediatric patients with solitary functioning kidney: a comparative analysis of congenital and acquired etiologies - Önal, Hülya Gözde; Semet, Yonca (Frontiers in Pediatrics, 2025)
IntroductionThis study aims to assess the clinical outcomes and kidney function in pediatric patients with a solitary functioning kidney (SFK) due to various causes. It focuses on evaluating the glomerular filtration rate (GFR) across five groups: renal agenesis, multicystic dysplastic kidney (MCDK), atrophic kidney, hypoplastic kidney, and patients who underwent nephrectomy due to bleeding, stones, infection, or tumor without having progressed to renal failure.MethodsA retrospective chart review was conducted on single kidneys of 396 patients seen at the pediatric nephrology clinic from January 2011 to June 2024. Descriptive statistics were used to summarize the data, with chi-square tests employed for categorical variables and t-tests or Mann–Whitney U-tests used for continuous variables. For comparisons involving more than two groups, ANOVA or Kruskal–Wallis tests were performed, followed by post-hoc Bonferroni tests.ResultsBaseline and final GFR values showed significant differences between the groups in the pre- and post-tests. The MCDK group had significantly lower GFR than the renal agenesis group and the remaining etiologies. Albumin levels were decreased in MCDK patients, whereas neutrophil levels were elevated in patients with renal agenesis. Hypertension or proteinuric activity did not exhibit significant variations in the frequency across these groups.DiscussionThis study highlights the importance of a personalized management approach for pediatric patients with an SFK, specifically those with MCDK, who are more likely experience early loss of kidney function. Minimizing the risks and improving the outcomes would require a routine, topical course of monitoring, along with appropriate treatment.